Secure e-Prescription Management System: Mitigating Blended Threat in IoBE - Kim, Deukhun; Kim, Heejin; Kwak, Jin (Computer Systems Science and Engineering, 2023)
New information and communication technologies (ICT) are being applied in various industries to upgrade the value of the major service items. Moreover, data collection, storage, processing, and security applications have led to the creation of an interrelated ICT environment in which one industry can directly influence the other. This is called the "internet of blended environments" (IoBE), as it is an interrelated data environment based on internet-ofthings collection activities. In this environment, security incidents may increase as size and interconnectivity of attackable operations grow. Consequently, preemptive responses to combined security threats are needed to securely utilize IoBE across industries. For example, the medical industry has more stringent information protection measures than other industries. Consequently, it has become a major target of attackers, as more clinician-patient interactions occur over the internet owing to COVID-19. Therefore, this study aims to acquire security for IoBE while focusing on the medical industry. Among the various types of medical ICT services, this study analyzes data flow and potential security threats from the e-prescription lifecycle perspective, which is highly utilized, strongly data-centric, and has numerous security issues. Based on our analysis, we propose a secure authentication and data-sharing scheme.
Keywords: Authentication scheme; Blended threats; Data storage applications; E-prescription; Information and Communication Technologies; Internet of blended environment; Management systems; Medical industries; New information and communication technologies; Security threats; Authentication scheme; blended threat; e-prescription; internet of blended environments